Titan the life of John D. Rockefeller - Chernow, Ron. (Blackstone Audio, 2013)
John D. Rockefeller, Sr.--history's first billionaire and the patriarch of America's most famous dynasty--is an icon whose true nature has eluded three generations of historians. Now Ron Chernow, the National Book Award-winning biographer of the Morgan and Warburg banking families, gives us a history of the mogul "etched with uncommon objectivity and literary grace . . . as detailed, balanced, and psychologically insightful a portrait of the tycoon as we may ever have" (Kirkus Reviews). Titan is the first full-length biography based on unrestricted access to Rockefeller's exceptionally rich trove of papers. A landmark publication full of startling revelations, the book will indelibly alter our image of this most enigmatic capitalist.
Unabridged
Keywords: Rockefeller, John D. (John Davison), 1839-1937.